Fusarium oxysporum –induced ABA signaling triggers root vascular remodeling for plant defense - Ana Cecilia Aliaga Fandino; Lucrezia Pinto; Antonio Serrano; Clara Sánchez-Rodriguez (Proceedings of the National Academy of Sciences, 2026)
Root vascular pathogens like Fusarium oxysporum (Fo) severely impact agriculture by colonizing the xylem, thereby disrupting the transport of water, nutrients, and signaling molecules within host plants. However, their effects on root growth and vascular development before xylem invasion, and the underlying molecular mechanisms, remain poorly understood. Here, we show that Fo triggers a rapid, systemic, abscisic acid (ABA) that seems to induce a developmental reprogramming in Arabidopsis that occurs prior to vascular colonization. This response is associated with root growth inhibition, disorganization of the root apical meristem, and alterations in xylem architecture. High-resolution imaging reveals that initial contact with Fo elevates root ABA levels, which parallels the modulation of key developmental pathways, including MIR165/PHB and VND7, which regulate vascular patterning and mediate premature xylem differentiation and remodeling. Phloem development is also affected, likely through disruption of CLE45–BAM3 signaling. Mutants impaired in endodermal ABA signaling, ELTPp:: abi1-1 , and secondary wall formation, cesa4, show constitutive elevated ABA levels, xylem defects, and enhanced resistance to Fo, suggesting that ABA-induced vascular remodeling contributes to the formation of structural barriers that limit infection. Additionally, Fo infection induces homogalacturonan demethylation in the stele, a modification associated with cell wall stiffening and reduced pathogen spread, which is constitutively observed in ELTPp:: abi1-1 . Overall, our findings reveal ABA-mediated vascular plasticity, including cell wall remodeling as a developmentally encoded root defense mechanism. They highlight how transient hormonal cues reprogram root architecture to limit pathogen invasion and suggest strategies for crop protection.